Study on the Relationship Between Symmetric Property of Optical Orbital Angular Momentum Spectrum and Critical Points of Phase in an Inhomogeneous Non-Random Media - Xu, Lingfei; Hong, Jun; Zhou, Zhichao; Ren, Tianrong (Frontiers in Physics, 2021)
In the aero-optic turbulent boundary layer (TBL), there exist very rich air flow structures that fall into a wide range of scales, with the smallest being roughly of the order of the optical wavelength. However, these fine spatial variations cannot be neglected when one is dealing with light propagation through such structures, since both the amplitude and phase of a light wave undergo modulations. In this study, we studied the influence of TBL on the angular momentum spectrum of light and found that there exists critical point of the azimuthal distribution of the disturbance phase that determines the symmetry properties of the expansion spectrum.